Nutrient foramen of humerus - Chalkoo, Sobia Ali; Lone, Parvaiz Ahmad; Shahdad, Shaheen; Bhat, Ghulam Mohammad (International Journal of Research in Medical Sciences, 2023)
Background: Humerus is a typical long bone of arm in human body extending from shoulders to elbow. Nutrient foramen is the small opening present in most of the bone of human body to transmit the nutrient artery which supplies nutrition to different parts of bone. The aim of the present study is to identify the number of nutrient foramen in dry humerus and to observe direction and allocation of the nutrient foramina. Methods: The present study was carried out in 60 dry humeri (23 rights and 37 lefts) collected from Department of Anatomy, Government Medical College Srinagar. Bones were examined with respect to the number, direction and anatomical location of nutrient foramen. Results: Out of 60 dry humeri, 36 (60%) had a single nutrient foramen, 14 (23.3%) had double, 7 (11.6%) had triple and 3 (5%) had no nutrient foramen. About 52% of the bones had nutrient foramen on the medial border, 40% on the Anteromedial surface, 3% on lateral border, 3% on posterior surface and 2% on the anterior border. Majority of the bones i.e., 81% have the nutrient foramen in the middle 1/3rd zone, 17% at the junction between middle 1/3rd zone and lower 1/3rd zone and 2% in the lower 1/3rd zone. Conclusions: By knowing the number and location of the nutrient foramina in humerus it is useful in preventing intra-operative injury of nutrient artery during orthopedic, plastic and reconstructive surgery.